Correlates of employment among men in substance use recovery: The influence of discrimination and social support. Issue 2 (3rd April 2022) - Hunter, Bronwyn A.; Jason, Leonard A.
Abstract: The purpose of the present study was to identify correlates of employment among men in substance use recovery, including recovery-related discrimination and social support. A cross-sectional sample of men ( N = 164) who lived in sober living homes located across the United States participated in the present study. Data were collected online and through mailed surveys. No socio-demographic variables were associated with employment status. Discriminant Analysis (DA) was conducted to understand how recovery-related discrimination and social support contributed to group separation (employed vs. not employed). Results from this analysis suggested that recovery-related discrimination was the driving force in classification, as men who were not employed had much higher recovery-related discrimination than men who were employed. Men who were not employed also had lower social support scores than men who were employed. Stigma and discrimination may play a large role in employment among former and current substance users. Treatment providers should discuss the impact of stigma on individuals while they are in treatment. However, additional research is needed to more fully understand the relations among discrimination, social support, and employment.